Understanding Ozone Formation and Carbonyl Contributions in the Seoul Metropolitan Area - Seung-Ha Lee; Ji-Seon Lee; Hyung-Min Lee; Hyeong-Ahn Kwon; Caroline R. Nowlan; Gonzalo González Abad; Rokjin J. Park; Ji-Hoon Park; Soyoung Kang; Hye-Jung Shin; Dai-Gon Kim; Jung-Min Park (Aerosol and Air Quality Research)
Abstract With strong air quality policies in place in China and South Korea in recent years, it is important to understand the changing situation to address the increasing surface ozone problem in Korea. We revisited the ozone formation condition and investigated the contribution of each component using observations of routinely measured volatile organic compounds (VOCs) and, for the first time, employed multiyear ground observations of carbonyl compounds (formaldehyde, acetone, and acetaldehyde) from the two sites in Seoul Metropolitan Area (SMA), Seoul and Incheon, during the 2016–2018 ozone season (May–September). We found a significant fraction of carbonyl compounds (formaldehyde) based on ground observations, accounting for 51% (38%) and 37% (25%) of the total VOCs in Seoul and Incheon. To determine the ozone production regime, we used OH reactivities of NOx and VOCs, including carbonyl compounds. We found that while Seoul is still in the NOx-saturated regime, Incheon is already almost in a transition regime regardless of including carbonyl compounds. Since both regions are changing toward the transition regime, it is important to manage the NOx and VOC concentrations in a balanced manner. We calculated the ozone formation potential (OFP) of each VOC species using Maximum Incremental Reactivity (MIR). The results showed that formaldehyde contributes the most to OFP both in Seoul and Incheon, accounting for 45% and 29%, respectively. This study highlights the importance of carbonyl compounds in ozone formation in SMA, and it is recommended that formaldehyde be monitored with finer time resolution at monitoring stations co-located with other VOC monitoring stations in SMA for more reliable investigations.